Lipid Extracts Obtained by Supercritical Fluid Extraction and Their Application in Meat Products - Branislav Šojić; Predrag Putnik; Bojana Danilović; Nemanja Teslić; Danijela Bursać Kovačević; Branimir Pavlić (MDPI AG, 2022)
Supercritical fluid extraction (SFE) has been recognized as the green and clean technique without any negative impact on the environment. Although this technique has shown high selectivity towards lipophilic bioactive compounds, very few case studies on the application of these extracts in final products and different food matrices were observed. Considering the recent developments in food science and the increasing application of supercritical extracts in meat products in the last decade (2012-2022), the aim of this manuscript was to provide a systematic review of the lipid extracts and bioactives successfully obtained by supercritical fluid extraction and their application in meat products as antioxidant and/or antimicrobial agents. Lipophilic bioactives from natural resources were explained in the first step, which was followed by the fundamentals of supercritical fluid extraction and application on recovery of these bioactives. Finally, the application of natural extracts and bioactives obtained by this technique as functional additives in meat and meat products were thoroughly discussed in order to review the state-of-the-art techniques and set the challenges for further studies.